“El rocoto” in times of globalization - Rodríguez Pastor, Humberto (2017)
The rocoto, among the varieties of peppers in Peru, is a very special spicy fruit between its sowers and consumers. In many Andeans places when they look for something that has fire and burns the palate, they only look for rocoto. And if it is in the home gardens it is a well-treated plant, and as it is of a sensitive spirit it must be treated with affection; Otherwise it does not bear pungent fruits, it is vengeful. If in the home garden there are many fruits are offered as gifts to relatives and neighbors and even rocoteras birds. There is a whole pedagogy to teach children how to consume it and on the other hand how it should be presented to the diners. The batán is a traditional companion of the rocoto and the millenary Andean cuisine. The rocoto is gaining importance is already achieved packaging and has global demand, is increasingly exported, He goes to other homes, but his Andean spirit does not migrate.